Implementasi Hukum Allah dalam Matius 22:34-40 bagi Pengembangan Komunitas Kristen - Dessy Handayani (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2020)
The reality of the practice of Christian life, which has gone through various events to the extreme of the rules which contain rules about the conventional church, this shows that the